Kontribusi Harga Diri Terhadap Kesejahteraan Subjektif Mahasiswa Yang Mengerjakan Skripsi Masa Pandemi COVID 19 Di Universitas Negeri Padang - Muhammad Fikri Hidayat (PAKAR Pendidikan, 2022)
Purpose of this study to determine the contribution of self esteem to subjective well being toward student’s undergraduate thesis during COVID 19 pandemic in Universitas Negeri Padang. This research is a quantitative research with correlational descriptive approach. This research used cluster random sampling technique. The samples in this study are 150 students. The data measuring instrument used the Likert scale consisting of two subjective well being is SWLS and PANAS scales and the self esteem scale. The technique of data analysis used simple linear regression analysis through IBM SPSS Statistic 20. Based on the findings of the research, it found that R-Square value of 0,327 with p 0,000 < 0,05 which means that Ha is accepted, it’s known that there is significant contribution of self esteem to subjective well being toward student’s undergraduate thesis during COVID 19 pandemic in Universitas Negeri Padang.